1988. Development of a Laboratory Stewardship Algorithm for Anaplasma phagocytophilum Polymerase Chain Reaction Testing. (26th November 2018) - Anahtar, Melis; Pattanayak, Vikram; Branda, John; Azar, Marwan M; Coffey, Kc; Eng, George; Rudolf, Joseph; Baron, Jason; Lewandrowski, Kent; Turbett, Sarah
Abstract: Background: Anaplasmosis often presents with fever and headache, and typical laboratory abnormalities include leukopenia and thrombocytopenia. Polymerase chain reaction (PCR) is the preferred diagnostic method. At our institution, Anaplasma PCR is overutilized, with a low positivity rate. To improve utilization, we performed a two-part study. Part 1 determined if complete blood count (CBC) values could exclude Anaplasma infection. A stewardship algorithm was implemented during part 2 of the study via a mock stewardship protocol. Methods: Part 1: Anaplasma PCR tests were included over a 3-year period. For each PCR result, white blood cell (WBC) and platelet (PLT) results from a sample collected near the time of PCR were evaluated in R Studio and GraphPad Prism. The significance of differences between PCR-positive and -negative cases was determined using the Mann–Whitney test. Cut-off values were chosen to maximize sensitivity of a screening algorithm for the detection of Anaplasma infection. Part 2: Mock stewardship was performed for 6 months. Screening criteria generated in phase 1 were applied to determine whether Anaplasma PCR would have been approved or rejected if stewardship were implemented based on laboratory and clinical parameters. Results: Part 1: 2166 PCR tests were included. Patients with a positive Anaplasma PCR had lower median WBC and PLT counts than those with a negative result (Figure 1). Combining criteria of a WBC ≥11 K/µL and PLT ≥300 K/µL provided rejection criteria with 100% sensitivity and 25% specificity after excluding immunocompromised or unstable patients (Figure 2). Part 2: 663 PCR tests were analyzed. Of those, 155 (23%) met CBC rejection criteria and were reviewed by committee. The committee mock refused 110 (71%) tests and mock accepted 49 (29%) based on clinical criteria. Of the patients with positive Anaplasma PCR, 1 met CBC rejection criteria and was mock refused by committee. On review, the patient was completing treatment for Anaplasmosis, indicating limited utility of testing. None of the 45 samples that were mock accepted by clinical criteria was positive by PCR, demonstrating no additional benefit of chart review. Conclusion: Implementation of a CBC-based stewardship algorithm would reduce unnecessary Anaplasma PCR testing and decrease cost by 23%. Disclosures: J. Baron, Roche Diagnostics: Possible Consulting Role—not finalized at this point, No compensation yet—compensation TBD